The KULULU Lead Strips: Economic Documents in Hieroglyphic Luwian - Hawkins, J. D.
Lead strip 1; Lead strip 2; Lead fragment 1 ; Lead fragment 3, unpubl., Lead strip 3, now joined to lead fragment 2. Addenda. Index: Personal names; Town names.